2016
DOI: 10.1021/acs.jproteome.6b00116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lysine Acetylation in Mycobacterium abscessus Using LC–MS/MS after Immunoprecipitation

Abstract: Mycobacterium abscessus (MAB), which manifests in the pulmonary system, is one of the neglected causes of nontuberculous mycobacteria (NTM) infection. Treatment against MAB is difficult, characterized by its intrinsic antibiotic drug resistance. Lysine acetylation can alter the physiochemical property of proteins in living organisms. This study aimed to determine if this protein post-translational modification (PTM) exists in a clinical isolate M. abscessus GZ002. We used the antiacetyl-lysine immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…These results suggested that GCRV infection induced wide changes in host cellular proteins at lysine acetylation level. Additionally, many lysine acetylation motifs identified in this study were also found in other eukaryotic and prokaryotic species [ 37 , 38 , 39 , 40 , 41 , 42 ], indicating that the lysine acetylation motifs are highly conserved among different species.…”
Section: Discussionsupporting
confidence: 66%
“…These results suggested that GCRV infection induced wide changes in host cellular proteins at lysine acetylation level. Additionally, many lysine acetylation motifs identified in this study were also found in other eukaryotic and prokaryotic species [ 37 , 38 , 39 , 40 , 41 , 42 ], indicating that the lysine acetylation motifs are highly conserved among different species.…”
Section: Discussionsupporting
confidence: 66%
“…Lys and Arg) are enriched at the ϩ1 and ϩ2 positions, in relation to the residue of acetylation, in the acetylomes of the two species. In comparison, Tyr is significantly enriched at the ϩ1 position whereas Lys or Arg is always located downstream of the ϩ2 position in the mycobacterium, drosophila and human acetylomes (12,13,92,93). H. mediterranei encodes twelve acyl-CoA synthetases.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli DH5␣ was grown at 37°C in Luria-Bertani (LB) medium. M. abscessus GZ002, a clinical isolate described previously (30), for which the whole genome and DNA methylome have been sequenced and analyzed (31), was used as the parental strain to construct the UAlMab strain. In addition, 20 new clinical strains of M. abscessus subsp.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 20 new clinical strains of M. abscessus subsp. abscessus isolated from Guangzhou Chest Hospital (Guangzhou, China), as identified by comparison of sequences of the 16S rRNA gene, the DNA gyrase subunit gene, and the DNA-directed RNA polymerase subunit ␤ gene ( Table 2 gives primer information), with their corresponding homologous genes in the reference strain M. abscessus ATCC 19977 (30), were investigated in this study. M. abscessus strains were grown at 37°C in Middlebrook 7H9 broth (Difco) supplemented with 0.05% Tween 80 and 10% oleic acid-albumin-dextrose-catalase (OADC; Difco), or on Middlebrook 7H11 agar (Difco) supplemented with 10% OADC.…”
Section: Methodsmentioning
confidence: 99%